17th International Conference on E-Society 2019 2019
DOI: 10.33965/es2019_201904l008
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Responses to Ads on Social Networking Sites: A Systematic Literature Review (Slr)

Abstract: A consequence of the growing number of the studies concerning ads on social networking sites, and the failure to provide an in-depth analysis of that stream of research is the need to adopt systematic approaches to assess and aggregate research outcomes. This article presents an up-to-date review of peer-reviewed relevant articles to consumers' responses to advertisements on SNSs. It helps to identify 100 relevant studies published in the period 2009-2017 from different management and social science fields; in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…According to Oh et al (2015), understanding different influence elements of consumers' behavior in social media ads is critical to the further understanding of overall consumer behavior development. Additionally, Deraz (2019) concluded that marketing insights on social networking sites cannot be generalized as a rule for one. Instead, different types of ads for different social platforms should be researched.…”
Section: Introductionmentioning
confidence: 99%
“…According to Oh et al (2015), understanding different influence elements of consumers' behavior in social media ads is critical to the further understanding of overall consumer behavior development. Additionally, Deraz (2019) concluded that marketing insights on social networking sites cannot be generalized as a rule for one. Instead, different types of ads for different social platforms should be researched.…”
Section: Introductionmentioning
confidence: 99%